What is hidden in the luggage? First assessments of illegal seashells gathering in Sardinia (Italy) - Stefania Coppa; Andrea Camedda; Giorgio Massaro; Sara Vencato; Franco Murru; Maria Tiziana Pinna; Davide Urrai; Antonio Casula; Maurizio Riccitelli; Giuseppe Andrea deLucia (Conservation Science and Practice, 2023)
Abstract Natural souvenirs collection has been identified as a driving force in biodiversity and habitat degradation of tropical marine ecosystems. This work considers this phenomenon in the Mediterranean region taking Sardinia (Italy), one of the most renowned tourism destinations, as a case study. The biological material seized at Cagliari‐Elmas Airport (years 2019–2020: 138 kg) was analyzed: 199 taxa were identified, gastropods (112 species, 7866 pieces) and bivalves (63 species, 34,218 pieces) resulted the most represented classes. Twenty‐two protected species were found in the tourists' luggage including Patella ferruginea and Pinna nobilis, the invertebrates most threatened with extinction in the Mediterranean Sea. This study demonstrates that the illegal collection of natural mementos is common in Sardinia, thus its relevance is not limited to tropical regions. Regulation, enforcement and compliance shortcomings emerged, highlighting the importance of strengthening stakeholders' collaboration for a deeper insight on this phenomenon and implementing effective conservation strategies.